Progress in the Management of Retinal Detachment Associated With Morning Glory Syndrome - Wu S; Wang W; Liu L; Wang W; Jiang K; Peng C; Sun H; Zhang J (Clinical Ophthalmology)
Suping Wu,1 Wenting Wang,2 Lei Liu,3 Wei Wang,2 Keke Jiang,2 Chuanzhi Peng,4 Huixin Sun,1 Jie Zhang2 1Department of Ophthalmology, Binzhou Medical College, Binzhou, Shandong, People’s Republic of China; 2Department of Ophthalmology, Weifang Eye Hospital, Weifang, Shandong, People’s Republic of China; 3Department of Ophthalmology, Guangdong Provincial People’s Hospital, Guangzhou, Guangdong, People’s Republic of China; 4Department of Ophthalmology, Shandong Second Medical University, Weifang, Shangdong, People’s Republic of ChinaCorrespondence: Jie Zhang, Department of Ophthalmology, Weifang Eye Hospital, Weifang, Shandong, People’s Republic of China, Email 15963688601@126.comAbstract: Morning glory syndrome (MGS) is a rare congenital optic disc malformation characterized by a distinctive funnel-shaped optic disc resembling a blooming morning glory flower, typically diagnosed in childhood or adolescence and primarily presenting unilaterally, although bilateral cases have been reported. The anomaly features an enlarged optic disc, radiating blood vessels, and surrounding excavation, leading to visual impairment that can range from mild to profound. The etiology of MGS is not fully understood but has been associated with genetic factors, particularly mutations in the PAX6 and PAX2 genes, which play critical roles in eye development. MGS is often linked with other ocular and systemic anomalies, including retinal detachment, a significant complication that may be exudative, tractional, or rhegmatogenous. Surgical interventions are generally employed to manage complications, especially retinal detachments, with procedures such as vitrectomy, paraoptic disc laser photocoagulation, and the use of silicone oil or gas tamponade, though success rates can vary widely. Long-term outcomes for patients with MGS largely depend on the severity of associated complications and the timing of interventions; while some individuals may attain reasonable visual function post-treatment, others may continue to experience challenges due to the underlying malformation and its consequences. Thus, MGS remains a complex condition requiring a multidisciplinary approach for effective management and enhanced patient outcomes, emphasizing the need for continued research into its genetic underpinnings and optimal treatment strategies to improve understanding and care for those affected.Keywords: morning glory syndrome, retinal detachment, vitrectomy, paraoptic disc laser photocoagulation